Methods of evaluation of autonomic nervous system function - Zygmunt, Agnieszka; Stanczyk, Jerzy (Archives of Medical Science, 2010)
Disturbances of the autonomic nervous system play a crucial role in the pathogenesis and clinical course of many diseases. Recently, rapid development has occurred in the clinical assessment of autonomic function. Various procedures have been described as diagnostic tools to monitor autonomic dysfunction. Some of them are mostly used for research purposes. Many, however, have found their place in routine clinical evaluation. Our paper presents selected methods of assessment of the autonomic nervous system with particular emphasis on those that are useful in diagnosis and treatment of diseases of the cardiovascular system. We discuss multiple tests based on cardiovascular reflexes, methods of studying heart rate variability as well as direct catecholamine measurements. Moreover, we outline tests of sudomotor function and microneurography.